Fluticasone furoate induced iatrogenic Cushing syndrome in a pediatric patient receiving anti-retroviral therapy. (6th April 2017) - van den Berg, S A A; van 't Veer, N E; Emmen, J M A; van Beek, R H T
Summary: We present a case of iatrogenic Cushing's syndrome, induced by treatment with fluticasone furoate (1–2 dd, 27.5 µg in each nostril) in a pediatric patient treated for congenital HIV. The pediatric patient described in this case report is a young girl of African descent, treated for congenital HIV with a combination therapy of Lopinavir/Ritonavir (1 dd 320/80 mg), Lamivudine (1 dd 160 mg) and Abacavir (1 dd 320 mg). Our pediatric patient presented with typical Cushingoid features (i.e. striae of the upper legs, full moon face, increased body and facial hair) within weeks after starting fluticasone furoate therapy, which was exacerbated after increasing the dose to 2 dd because of complaints of unresolved rhinitis. Biochemical analysis fitted iatrogenic Cushing's syndrome, with a repeatedly low cortisol (<0.03 µM, ref 0.14–0.60 µM) and low ACTH (9 pg/mL, ref 9–52 pg/mL) without signs of adrenal insufficiency. No other biochemical abnormalities that could point to adrenal or pituitary dysfunction were detected; electrolytes, thyroid and gonadal function, and IGF-1 were within the normal range. Pharmacogenetic analysis revealed that the pediatric patient carried the CYP3A4 *1B/*1G and CYP3A5 *3/*3 genotype (associated with a partial and complete loss of enzyme activity, respectively) which is associated with the development of iatrogenic Cushing's syndrome in patients treated for HIV due to the strong inhibition of CYP3 enzymes by Ritonavir. Upon discontinuation of fluticasone treatment, the pediatric patient improved both clinically and biochemically with normalisation of cortisol and ACTH within a couple of weeks. Learning points: Fluticasone therapy may induce iatrogenic Cushing's syndrome in a patient treated with anti-retroviral therapy. Pharmacogenetic analysis, in particular CYP3A genotyping, provides useful information in patients treated for HIV with respect to possible future steroid treatment. Fluticasone furoate is not detected in the Siemens Immulite cortisol binding assay.